From legal object to legal subject: changing conceptions of criminal animals in fourteenth- and fifteenth-century France - MacGregor, LB (2021)
This thesis concerns cases against harm-causing animals which occurred in France in the fourteenth and fifteenth centuries. I have focused on Eastern and Northern France, particularly Burgundy and areas around Paris. As a subject deemed at best a curiosity and at worst a remnant of a superstitious age, my purpose is to suggest how we might more effectively read, interpret, and understand cases where an animal that had killed a human became subject to the judicial process.